Effects of Mycorrhizal Fungi on Vigna Radiata Growth in Soil Differing in Fertilizer Concentration - Ming Sum Jessica Cheng (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2017)
Mycorrhizal fungi form mutualistic relationships with the roots of some plants, allowing the plant access to nutrients and minerals while the fungi obtain food from the plant. Given that this relationship is beneficial to the plant, this paper investigates the nature of the impact of presence of mycorrhizal fungi on the growth of Vigna radiata (mung beans) in soil of differing chemical environments. Through comparing the stem lengths of plants seven days after germination, it is found that in soil with 0.0% fertilizer, the presence of locally collected, unclassified mycorrhizal fungi impacts the growth of Vigna radiata negatively; in intermediate fertilizer concentrations (1.0%, 1.1%, 1.2%) there is no significant effect; at higher fertilizer concentrations, the mycorrhizal fungi aid in the plants’ survival and growth. This paper concludes that in nutrient-deficient environments, the mycorrhizal fungi compete for nutrients with the plant, yet benefits the plant by stabilizing its growth when nutrients are available. Due to the unclassified nature of the mycorrhizal fungi used in this experiment, this investigation is very preliminary and opens itself to many more topics of research in the future.
Keywords: mycorrhizal fungi